IMPLEMENTASI METODE DEMONSTRASI PADA MATA KULIAH KETERAMPILAN DASAR MENGAJAR MAHASISWA PENDIDIKAN AGAMA ISLAM UNIVERSITAS ISLAM MALANG - Nova Anjarwati; Rosichin Mansur; Fita Mustafida (VICRATINA, 2022)
Learning the Basic Teaching Skills Course for PAI UNISMA uses the demonstration method, which the lecturer begins the lesson by briefly, clearly and concisely explaining the important points about the learning material. The program, application, and outcomes of the demonstration technique are the main research interests. With the case study research design, a qualitative research methodology is applied. Observation, interviews, and documentation are all forms of data collecting. Meanwhile, data analysis uses Miles & Huberman analysis. The results are: 1) The demonstration method implementation program includes the formulation of learning objectives and preparing the Learning Implementation Plan. 2) The implementation of the demonstration method begins by explaining the one-semester learning design about the eight basic teaching skills. However, in practice, there is no seating position arrangement because teaching uses zoom via an online system caused by the Covid-19 pandemic and ends with giving assignments in the form of teaching practices in the field. 3) The results of the implementation of the demonstration method are that students know more about theory and practice in teaching and make student learning outcomes very good.